Does drinking modify the relationship between men's gender‐inequitable attitudes and their perpetration of intimate partner violence? A meta‐analysis of surveys of men from seven countries in the Asia Pacific region. (28th April 2021) - Laslett, Anne‐Marie; Graham, Kathryn; Wilson, Ingrid M.; Kuntsche, Sandra; Fulu, Emma; Jewkes, Rachel; Taft, Angela
Abstract: Background and aims: Although men's alcohol misuse and less gender‐equitable attitudes have been identified as risks for perpetration of intimate partner violence (IPV), less is known about how men's gender‐equitable attitudes and drinking act together to increase risk of IPV. This study aimed to assess the independent relationships of lower gender‐equitable attitudes and drinking to perpetration of IPV and their interaction among men in seven countries. Design: Secondary analysis of the United Nations Multi‐Country Study on Men and Violence (UNMCS) and Nabilan Study databases consisting of (1) unadjusted and adjusted logistic regression to measure the association of perpetration of IPV with gender‐equitable men (GEM) scale score and regular heavy episodic drinking (RHED) and (2) meta‐analyses of prevalence and effect estimates adjusted for country‐level sites and countries. Setting and participants: A total of 9148 ever‐partnered 18–49‐year‐old men surveyed in 2011–15 from 18 sites in Bangladesh, Cambodia, China, Indonesia, Papua New Guinea, Sri Lanka and Timor Leste. Measurements: The outcome variable is reported perpetration of physical or sexual IPV in the previous year. Independent variables: GEM scale scores; RHED, defined as six or more drinks in one session at least monthly (compared with other drinkers and abstainers). Findings: Pooled past‐year prevalence of perpetration of IPV was 13% [95% confidence interval (CI) = 9–16%]. GEM scores and RHED were independently associated with perpetration of IPV overall and in most sites. Pooled odds ratios (ORs) for perpetration of IPV with less equitable GEM scores were 1.07 (95% CI = 1.04, 1.09) and with RHED were 3.42 (95% CI = 2.43, 4.81). A significant interaction between GEM score and RHED ( P  = 0.001) indicated that RHED increased the relationship of less gender‐equitable attitudes and perpetration of IPV. Conclusion: Both gender‐inequitable attitudes and drinking appear to be associated with perpetration of intimate partner violence by men, with regular heavy episodic drinking increasing the likelihood of intimate partner violence among men with less equitable gender attitudes.